2022
DOI: 10.1002/ese3.1344
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of avoidable and unavoidable exergy destructions in a parallel double‐effect LiBr–water absorption cooling system

Abstract: A parametric study has been carried out based on advanced exergy assessment for a parallel double‐effect LiBr–water absorption chiller. The advanced exergy method provides the real potential of the equipment for improvement in the system by recognizing the avoidable irreversibilities. The sensitivity analysis of various parts of the exergy destruction (endogenous avoidable, endogenous unavoidable, exogenous avoidable, and exogenous unavoidable) in system components and the overall performance (coefficient of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…COP of the DEARC system is defined as follows 57 : COPitalicDEARC=Q̇coolingtrueQ̇italicHPGitalicDEARC+trueẆitalicpumpitalicDEARC, ${{COP}}_{{DEARC}}=\frac{{\dot{Q}}_{{cooling}}}{{\dot{Q}}_{{HPG}}^{{DEARC}}+{\dot{W}}_{{pump}}^{{DEARC}}},$where trueW˙italicpumpitalicDEARC ${\dot{W}}_{{pump}}^{{DEARC}}$ is the power consumption of the DEARC pump, trueQ˙italicHPGitalicDEARC ${\dot{Q}}_{{HPG}}^{{DEARC}}$ represents input the energy to the weak solution in HPG and trueQ˙italiccooling ${\dot{Q}}_{{cooling}}$ is the cooling power provided by the evaporator, calculated as follows: trueQ̇italicHPGitalicDEARC=trueṁitalicHPGitalicORChHPG,initalicORChHPG,outitalicORC, ${\dot{Q}}_{{HPG}}^{{DEARC}}={\dot{m}}_{{HPG}}^{{ORC}}\left({h}_{{HPG},{in}}^{{ORC}}-{h}_{{HPG},{out}}^{{ORC}}\right),$ trueQ̇italiccooling=trueṁitalicevitalicDEARChev,outitalicDEARChev,initalicDEARC, ${\dot{Q}}_{{cooling}}={\dot{m}}_{{ev}}^{{DEARC}}\left({h}_{{ev},{out}}^{{DEARC}}-{h}_{{ev},{in}}^{{DEARC}}\right),$where truem˙italicHPGitalicORC ${\dot{m}}_{{HPG}}^{{ORC}...…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…COP of the DEARC system is defined as follows 57 : COPitalicDEARC=Q̇coolingtrueQ̇italicHPGitalicDEARC+trueẆitalicpumpitalicDEARC, ${{COP}}_{{DEARC}}=\frac{{\dot{Q}}_{{cooling}}}{{\dot{Q}}_{{HPG}}^{{DEARC}}+{\dot{W}}_{{pump}}^{{DEARC}}},$where trueW˙italicpumpitalicDEARC ${\dot{W}}_{{pump}}^{{DEARC}}$ is the power consumption of the DEARC pump, trueQ˙italicHPGitalicDEARC ${\dot{Q}}_{{HPG}}^{{DEARC}}$ represents input the energy to the weak solution in HPG and trueQ˙italiccooling ${\dot{Q}}_{{cooling}}$ is the cooling power provided by the evaporator, calculated as follows: trueQ̇italicHPGitalicDEARC=trueṁitalicHPGitalicORChHPG,initalicORChHPG,outitalicORC, ${\dot{Q}}_{{HPG}}^{{DEARC}}={\dot{m}}_{{HPG}}^{{ORC}}\left({h}_{{HPG},{in}}^{{ORC}}-{h}_{{HPG},{out}}^{{ORC}}\right),$ trueQ̇italiccooling=trueṁitalicevitalicDEARChev,outitalicDEARChev,initalicDEARC, ${\dot{Q}}_{{cooling}}={\dot{m}}_{{ev}}^{{DEARC}}\left({h}_{{ev},{out}}^{{DEARC}}-{h}_{{ev},{in}}^{{DEARC}}\right),$where truem˙italicHPGitalicORC ${\dot{m}}_{{HPG}}^{{ORC}...…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…The AR system requires an energy source to evaporate the refrigerant, for which solar energy can be used. 24,25 Solar energy is the most abundant renewable energy source that can provide unlimited thermal energy for the AR system by incorporating a solar farm comprising several collectors. 26 However, no study has evaluated this promising alternative for cooling the turbine's inlet air in a combined gas-steam cycle power plant.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that AR systems are more desirable in areas with ambient temperatures greater than 25°C and relative humidity higher than 40%. The AR system requires an energy source to evaporate the refrigerant, for which solar energy can be used 24,25 . Solar energy is the most abundant renewable energy source that can provide unlimited thermal energy for the AR system by incorporating a solar farm comprising several collectors 26 .…”
Section: Introductionmentioning
confidence: 99%